Adaptive priority-based fair-resource allocation for MIMO-OFDM multicast networks. (2019) - Hindumathi, Voruganti; Reddy, Katta Rama Linga
In MIMO-OFDM multicast networks, sub-carrier allocation for real-time and non-real time users is complex due to delay and throughput issues. In order to overcome these issues, in this paper, we propose to develop a priority-based fair-radio resource allocation for MIMO-OFDMA-based multicast system. Initially, the multicast groups are classified as RT, NRT and BE. Then priorities are assigned for the groups based on the QoS requirements such as delay tolerance, packet dropping rate and transmission rate. When the priority value of a group is greater than the priority threshold, then the resource is allocated to the relevant group as per fair resource allocation technique. Overall this technique improves the sub-carrier allocation for real-time and non-real time users in terms of spectral efficiency and fairness. By simulation results, we show that the proposed technique enhances the average throughput, spectral efficiency, sub-carrier distribution for each class of users.